Leveraging retinal vascular features in non-invasive, early diagnosis of preeclampsia - Kimia Heydari; Elizabeth J. Enichen; Ben Li; Joseph C. Kvedar (npj Digital Medicine)
Wu et al.’s recent article, “Noninvasive early prediction of preeclampsia in pregnancy using retinal vascular features,” documents significant differences in retinal vascular features among women who develop preeclampsia and those with normotensive pregnancies. These findings provide evidence that retinal screening has the potential to be used as a low-cost, non-invasive screening strategy to support the earlier detection, prevention, and treatment of preeclampsia.